IMA Genome – F19 - Janneke Aylward; Andi M. Wilson; Cobus M. Visagie; Joseph Spraker; Irene Barnes; Carla Buitendag; Callin Ceriani; Lina Del Mar Angel; Deanné du Plessis; Taygen Fuchs; Katharina Gasser; Daniella Krämer; et al. (IMA Fungus)
Abstract The pace at which Next Generation Sequence data is being produced continues to accelerate as technology improves. As a result, such data are increasingly becoming accessible to biologists outside of the field of bioinformatics. In contrast, access to training in the methods of genome assembly and annotation are not growing at a similar rate. In this issue, we report on a Genome Assembly Workshop for Mycologists that was held at the Forestry and Agricultural Biotechnology Institute (FABI) at the University of Pretoria, South Africa and make available the 12 draft genome sequences emanating from the event. With the aim of making the process of genome assembly and annotation more accessible to biologists, we provide a step-by-step guide to both genome assembly and annotation, intended to encourage and empower mycologists to use genome data in their research.